DAMPAK DEFISIT AIR TERHADAP KARAKTER MORFOLOGI TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq.) VARIETAS DyxP DUMPY DI PEMBIBITAN UTAMA - Sri Murti Tarigan; Eka Bobby Febrianto; Hussein Abdillah (Bernas : Jurnal Penelitian Pertanian, 2019)
Oil Palm (Elaeis guineensis Jacq.) Is one of the important plantation crops in Indonesia. This plant produces vegetable oils that are important for the food industry and for fuel (biodiesel). Oil palm produces the highest oil unity of area compared to other types of plants with oil potential of around 6-7 tons/ha/year. The research was carried out in the greenhouse of the Plantation Agribusiness Institute of Higher Education (STIPAP). The study period was 6 months from September to March 2018. This study also used a non-factorial randomized block design with 3 times replication, the number of polybags per treatment was 3. Parameter tests were arranged on the variance list and Duncan's Multiple Range Test (DMRT) was tested level of 5%. The results of this study indicate that DyxP DUMPY varieties have good resistance to water stress. Dy×P Dumpy varieties were relatively more adaptable and gave better growth compared to other varieties in the condition of giving 1000 ml of water which was shown in observing the height increase of plants, increasing the number of leaves, increasing the diameter of the stem.